Phylogenetic reappraisal and epitypification of Laccaria macrocystidiata (Hydnangiaceae, Basidiomycota) - Dovana, Francesco; Moreno, Gabriel; Para, Roberto; Lavorato, Carmine; Mucciarelli, Marco (Phytotaxa, 2021)
Laccaria macrocystidiata, a marasmioid species, originally described as Laccaria affinis f. macrocystidiata from Central Italy, was synonymised with the North American taxon Laccaria laccata var. pallidifolia, but only on a morphological basis. In this paper, the independent position of L. macrocystidiata from L. laccata var. pallidifolia and other species of Laccaria is pointed out on the basis of ITS-LSU phylogenetic analyses. According to our results, Laccaria macrocystidiata var. longispinosa is considered a synonym of Laccaria macrocystidiata. Laccaria macrocystidiata holotype consists of only one basidioma in poor condition; thus, a new epitype from an Italian collection was designated.